Evaluation of the Boys’ Brigade program based on the CIPPO model in secondary schools - Ndruru, Perhatian; Dwikurnaningsih, Yari (Indonesian Research Journal in Education |IRJE|, 2026)
This study evaluates the effectiveness of the Boys’ Brigade (BB) program as a character and leadership development model at Lentera Harapan Curug Junior High School using the CIPPO framework (Context, Input, Process, Product, and Outcome). A qualitative case study approach was employed, with data collected through interviews, observations, and document analysis involving school leaders, instructors, and stakeholders. The findings show that the program aligns well with the school’s character education goals. Human resources and curriculum support are adequate, though facilities remain limited, which may hinder the program’s full potential and its ability to provide comprehensive educational experiences. The implementation emphasizes experiential learning but lacks formal instructional planning and structured assessment. The program has contributed positively to students’ discipline, spirituality, and leadership, while also strengthening school culture. These findings highlight the importance of systematic evaluation and administrative support in enhancing the effectiveness and sustainability of character education programs.